1994
DOI: 10.1002/pro.5560030409
|View full text |Cite
|
Sign up to set email alerts
|

DNA binding and bending by the transcription factors GAL4(62*) and GAL4(149*)

Abstract: The DNA binding domain of the GAL4 transcription factor from yeast is located in the N-terminal60 residues of the polypeptide of 881 amino acids. This domain binds 2 Zn ions, which form a binuclear cluster, ZnzC,, with 6 C residues, two of which bridge the 2 metal ions (Gardner KH et al., 1991, Biochemistry 3 0 11292-1 1302). Binding of Zn or Cd to GAL4 induces the conformation of the protein necessary to recognize the specific DNA sequence, UASG, to which GAL4 binds as a dimer. Gel retardation assays have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…Zinc exchange rates observed here are between 1 and 2 orders of magnitude faster than those reported for the Gal4(62*) protein, a shorter fragment, with free zinc ions (24). In this study, an examination revealed biphasic kinetics, with t 1/2 ϭ 24 h and t 1/2 ϭ 96 h at 4ЊC and pH 7.0 for both processes.…”
Section: Resultssupporting
confidence: 41%
See 2 more Smart Citations
“…Zinc exchange rates observed here are between 1 and 2 orders of magnitude faster than those reported for the Gal4(62*) protein, a shorter fragment, with free zinc ions (24). In this study, an examination revealed biphasic kinetics, with t 1/2 ϭ 24 h and t 1/2 ϭ 96 h at 4ЊC and pH 7.0 for both processes.…”
Section: Resultssupporting
confidence: 41%
“…Preparation of Gal4. The storage buffer (10 mM Tris⅐Cl͞150 mM sodium chloride͞1 mM 2-mercaptoethanol͞10 M Zn 2ϩ , pH 8) of the bacterially expressed Gal4(149*) fragment (24) was exchanged against 10 mM Tris⅐Cl͞15 mM sodium chloride, pH 8.6, using Centricon-10 centrifugal concentrators (Amicon). At least 15 mM sodium chloride is necessary to solubilize the protein fragment at pH 8.6.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DNA fragments were 32 P-labeled with [g-32 P]ATP using phage T4 polynucleotide kinase. Gel mobility shift assays were done as described with the exception that poly(dIdC) was used as the competitor DNA (Rodgers & Coleman, 1994).…”
Section: Gel Electrophoretic Mobility-shift Assaysmentioning
confidence: 99%
“…As shown in Figure 1, three types of molecular recognition mechanisms were employed to facilitate the preparation of TF-encapsulated SNP (TF·DNA⊂SNPs). First, the specific binding (the dissociate constant K d ≈ 10 nM) [15] between GAL4-VP16 (TF) and pG5E4T-Fluc (DNA) led to the formation of an anionic TF·DNA complex. Second, the Ad/CD-based molecular recognition ( K =1.1 × 10 5 M −1 ) [16] was utilized to form the SNP vectors with cationic hydrogel cores.…”
mentioning
confidence: 99%